The Degree of Availability of Critical Thinking Skills in the Science Curriculum for the Fourth Basic Grade in the Syrian Arab Republic (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Arts Humanities Series, 2026)
The research aimed to analyze the content of the science book for the fourth basic grade, to know determine degree of includes critical thinking skills, and the researcher adopted the method of content analysis from the descriptive method, while the research sample was the science book for the second semester, which contains only three units, and the course for the fourth basic grade from the Syrian Ministry of Education for 2024/2025, and the research tool was an analysis card for critical thinking skills, based on a list prepared by the researcher. The researcher concluded that the most critical thinking skills (second chapter) are the skill (interpretation) with repetitions of (79), with a high degree (50.32%), and in the second came the skill (inference) which repetitions of (47), with a moderate degree (29.94%), then came in the third, fourth and fifth the skills (evaluation, comparison, discrimination) with repetitions of (13), (10), (8), and with a low degree (8.28%), (6.37%), (5.1%).     The most suggestions: Focusing on critical thinking skills in a balanced manner in the science textbook, and training learners in critical thinking skills.
Keywords: Critical Thinking Skills, Science Curriculum, Fourth Basic Grade